A Case Report of Non-Traumatic Spinal Cord Injury Following Large Cervicodorsal Syringohydromyelia - Rajeev Kumar Singh; Prince Rohilla; Zubina Khan; Nitika Roy; Shazia Mattu (International Journal of Physiotherapy)
Background: Patients having cervicodorsal syrinx are at an increased risk of sustaining a complete spinal cord injury resulting in poor prognosis. Current data on the efficacy of physical therapy for this condition is limited. In this study, rehabilitation aimed to maximize functional independence in ADLs. Subsequently, emphasis was placed on improving general fitness, coordination, and balance. Case Summary: A female aged 38 years with a history of seizures and tubercular meningitis sustained a non-traumatic spinal cord injury as a result of large cervicodorsal syringohydromyelia. She underwent lumbo-peritoneal shunting surgery. Postoperatively, the patient experienced paralysis and loss of sensation in the lower limbs, along with urinary incontinence. The physiotherapy protocol was planned using a comprehensive neurological rehabilitation strategy so as to relieve her symptoms and improve her QoL. NMES was implemented after 4 months to enhance motor control and facilitate active assisted movement. Sessions were conducted 3-4 times per week. Outcome measures: ASIA Scale, ASIA impairment Scale, SCIM, Borg rate of perceived exertion, QoL index SCI version-III, modified functional reach test, Spinal Cord Injury Functional Ambulation Index, and Karnofsky performance index were outcomes used to analyse the efficiency of numerous medications and to assess patient prognosis. Conclusion: The patient's level of functional independence increased, i.e., she was able to get out of bed and move to a chair, stand and walk with a walker, and perform her personal hygiene tasks (eating, dressing, using the bathroom, bathing, etc.). Further research is needed to evaluate potential benefits and optimize treatment protocols.